Genetic variation of some species of the genus Tagetes sp. Using PCR-RAPD in Iraq - Almehanya, Farqad Hayder (International Journal Papier Advance and Scientific Review, 2023)
Random Amplified Polymorphic DNA (RAPD) indicators were carried out to prepare the genetic fingerprints of six species of the genus Tegates. The discrepancies between the replicates of each species (their numbers and molecular sizes) were revealed after the replicates of the samples were migrated onto agarose gel and stained with ethidium bromide. 10 primers were selected, which showed different replication products among the studied species, as those primers showed 63 polymorphic bands out of 468 total bands. Each selected starter produced between 23 bands (OPD-18) to 78 bands (OPF-04). The largest number of divergent bands (15 bands) generated by the primer OPD-13, while it appeared that the least number of divergent bands (3 bands) which was generated by the primer OPD-18. The primer efficiency ranged from 0.20 in (OPD-13) to 0.09 in (primer OPA-04). It was found in this study that the primer OPD-13 had the highest discrimination ability, while the primer OPD-18 had the lowest value of the discrimination ability. The lowest genetic dimension was (0.3755) between the two species T. erecta and T. patula, while the largest genetic dimension was (0.8466) between the two species T. patula and T. tenuifolia. The phylogenetic tree through the unweighted pair-group method of arithmetic means (UPGMA) that is, based on the tree of phylogenetic relationships revealed two main genetic groups. The general analysis of the results showed that the genetic relationships between the species of the genus Tegates are related to some morphological traits as well as to the original origin and at the level of molecular genetics.